True to our native land : an African American New Testament commentary - Blount, Brian K., 1956-; Byron, Gay L.; Powery, Emerson B. (Minneapolis : Fortress Press, 2024)
"True to Our Native Land is a pioneering commentary of the New Testament that sets biblical interpretation firmly in the context of African American experience and concern. The second edition includes updated commentaries and essays"--
Keywords: Bible. -- Commentaries; Bible. -- Criticism, interpretation, etc; Bible. -- Black interpretations; African Americans -- Religion; Commentaries